2002
DOI: 10.1097/00007890-200210270-00009
|View full text |Cite
|
Sign up to set email alerts
|

Association between hepatitis C virus infection and development of posttransplantation diabetes mellitus in renal transplant recipients12

Abstract: HCV infection was associated with the development of PTDM, in addition to family history and increased age. The rate of autoantibodies against pancreatic cells was not increased in patients with HCV, which suggested that nonimmunologic mechanisms were likely to have a role in the pathogenesis of PTDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
2
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 24 publications
3
20
2
1
Order By: Relevance
“…Several authors have reported the presence of an association between HCV infection and the development of posttransplantation diabetes mellitus, both after liver transplantation (27) and RT (28,29). None of our patients presented with posttransplantation diabetes mellitus.…”
Section: Discussionmentioning
confidence: 49%
“…Several authors have reported the presence of an association between HCV infection and the development of posttransplantation diabetes mellitus, both after liver transplantation (27) and RT (28,29). None of our patients presented with posttransplantation diabetes mellitus.…”
Section: Discussionmentioning
confidence: 49%
“…In this study, a significant interaction (P = 0.0001) was found between presence of HCV and use of tacrolimus, since in the HCV-positive group, T2D occurred more often in tacrolimus-treated than cyclosporine A-treated patients (57.8% vs 7.7%; P < 0.0001) [55] . Most subsequent studies confir med this robust association [56][57][58][59][60][61][62][63] , with some exceptions [21,[64][65][66] . Thus, in a recent meta-analysis of 10 studies, the pooled relative risk for post-KT T2D was 2.73 (95% CI: 1.94-3.83) [67] .…”
Section: Association Between Hcv and T2dmentioning
confidence: 95%
“…In addition to ongoing HCV infection, risk factors for developing T 2 D a f t e r K T a r e f a m i l y h i s t o r y o f T 2 D [ 5 5 , 6 0 ] , age [57,59,61,62] , use of tacrolimus [55,59,60,62,63] , smoking [61] , overweight/obesity [62,63] , African-American ethnicity [62] and pre-transplantation impaired fasting glucose [63] . Thus, there exists a significant increase of the risk of post-KT T2D in HCV-positive recipients, especially in the first 2 mo after transplantation [57] . Since T2D and its complications are a leading cause of mortality after KT, it is easy to understand that every effort should be made to clear HCV with antiviral therapy in the pre-KT period, whenever this is feasible.…”
Section: Association Between Hcv and T2dmentioning
confidence: 99%
“…This relation was not noted in our study and some older reports. 13,26 This may be explained by the small number of patients on tacrolimus without steroids and the short posttransplant duration of recipients on steroid-free immunosuppression because we used a different immunosuppressive protocol.…”
Section: Discussionmentioning
confidence: 99%